Viewpoint on social-emotional learning of 5-10 year olds as area of predicting their academic success: Research data obtained in Western countries - Lieģeniece, Daina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article aims to provide an overview of research data analysis made in Western countries (namely in the US and the United Kingdom) on Social – Emotional Learning and academic success. The article consists of two parts. Part One provides a basis for understanding what social and emotional learning is by analysing some issues of socialemotional competencies. Part Two discusses the issue of associations of SEL with Academic Success. It is done with the aim to show the nursery and primary school teachers how important it is to have a clear understanding of the chosen approaches to address the problems of social-emotional competencies and academic success.